2021
DOI: 10.1021/acs.energyfuels.1c02379
|View full text |Cite
|
Sign up to set email alerts
|

Ni–Mo2C Nanocomposites as Highly Efficient Catalysts for Hydrogen Generation from Hydrolysis of Ammonia Borane

Abstract: Supported non-noble metal nanomaterials have attracted much interest due to their promising application prospects in heterogeneous catalysis. γ-Al2O3-supported Ni–Mo x C catalysts have been synthesized using an impregnation method, followed by the carburization at 993 K under a 5% H2/Ar flow. The synthesized NiMo x C/γ-Al2O3 catalysts are characterized and first tested in the hydrolysis of ammonia borane (NH3BH3, AB) at 298 K. The X-ray photoelectron spectra analysis shows that the incorporation of Mo x C can … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 49 publications
1
10
0
Order By: Relevance
“…SI Table S2 also listed some Ni-based catalyst for AB hydrolysis reported in the literatures. Among them, Ni/Ti 3 C 2 T x -4 exhibited the best catalytic activity. …”
Section: Results and Discussionmentioning
confidence: 99%
“…SI Table S2 also listed some Ni-based catalyst for AB hydrolysis reported in the literatures. Among them, Ni/Ti 3 C 2 T x -4 exhibited the best catalytic activity. …”
Section: Results and Discussionmentioning
confidence: 99%
“…The catalytic activity was determined by measuring the H 2 generation rate from AB hydrolysis. All of the experiments were conducted using a thermostatic magnetic stirring apparatus, and H 2 generated was collected by a typical water displacement method, as reported in the literature . Typically, a suspension solution containing 10 mg of catalyst and 2.5 mL of deionized water was placed in a round-bottom flask (50 mL), followed by sonication for 2 min, and then was preheated at 298 K in a thermostatic water bath under continuous stirring.…”
Section: Methodsmentioning
confidence: 99%
“…Moreover, in our previous study, the ability of Mo 2 C to activate the water is also confirmed by the experimental studies on the NiMo x C/γ-Al 2 O 3 system. 32 However, a comparative study of α-MoC and Mo 2 C is not carried out so far. Therefore, an experimental or theoretical study would be made to explore the crystalline phase effect of Mo x C on the catalytic behavior of AB hydrolysis and subsequently establish the structure−activity relationship.…”
Section: Nh Bhmentioning
confidence: 99%
See 1 more Smart Citation
“…AB was applied in fuel cells in two ways: one is as a hydrogen storage material to produce H 2 [16][17][18][19][20] and another is as an anode fuel directly. 21,22 As the indirect application of AB, the dehydrogenation of AB has been widely studied in recent years owing to its high gravimetric hydrogen density (19.6 wt% H), and there are three methods to promote the dehydrogenation of AB, including thermolysis, [23][24][25][26] hydrolysis, 16,[27][28][29] and alcoholysis. 17,[30][31][32] The rational design of catalysts is the key to accelerating the production of H 2 , especially with the hydrolysis approach.…”
Section: Introductionmentioning
confidence: 99%